If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(3 + 2r) = -36r (3 * -5 + 2r * -5) = -36r (-15 + -10r) = -36r Solving -15 + -10r = -36r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '36r' to each side of the equation. -15 + -10r + 36r = -36r + 36r Combine like terms: -10r + 36r = 26r -15 + 26r = -36r + 36r Combine like terms: -36r + 36r = 0 -15 + 26r = 0 Add '15' to each side of the equation. -15 + 15 + 26r = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 26r = 0 + 15 26r = 0 + 15 Combine like terms: 0 + 15 = 15 26r = 15 Divide each side by '26'. r = 0.5769230769 Simplifying r = 0.5769230769
| 3(k-8)=k+9 | | 0.8-8=0.2a | | 90+0.25*x=3000-x | | 4(-19+n)=-40 | | 5n-4=n-8 | | 1.6x+14.2=3.5x-1 | | 14w=6w+40 | | 2+.10(30)=y | | 5+g=2 | | 90+0.25*x=1000-x | | 2+i=4 | | 3a+4a=9 | | 12x^2+12=25 | | 8+11b=-146 | | 3.95+.05(30)=y | | 15x+3-30x+6=2 | | 1.3+5.2=3.1x-2 | | -12(8+v)=36 | | 4(x+10)+5x=9x-40 | | 8j=6 | | 3tan^2(x)-5tan(x)-2=0 | | 90+0.25x=0 | | -38=-28+x | | 4+2x=4(2x+2)-7(x-2) | | -115=5n | | -8+2w=0 | | 32+(5+x)=20 | | 3.95+.05(10)=y | | -10=x+(-20) | | 0-5y=13 | | -8n=-192 | | 3.95+.05(10)= |